Implementation of Circuit Training and Interval Training Exercises on Improving Football Dribbling Skills in Seventh Grade Junior High School Students - Putra, Yudha Purnama; Imansyah, Farizal; Kristina, Putri Cicilia (PPSDP International Journal of Education, 2024)
Football is a sport that requires a combination of good physical, technical, and tactical skills. One of the important technical skills in football is dribbling, which is the ability to control and manipulate the ball with the feet. Improving dribbling skills is a major focus in physical training for junior high school students, because it not only improves individual performance but also the overall contribution of the team in the game. This study explored the effects of two different training methods, namely circuit training and interval training, on the dribbling skills of junior high school students. Good dribbling skills are a crucial aspect in the technical development of football players at their developmental stage. Using an experimental approach, students were randomly selected to participate in training twice a week for 10 weeks. Dribbling ability evaluations were conducted before and after the training period to compare the effects of the two training methods. These findings are expected to provide deeper insight into the effectiveness of technical training in improving junior high school students’ dribbling skills in an educational setting.